The Stomach as an Energy Homeostasis Regulating Center. An Approach for Obesity - Al-Massadi, Omar; Pardo, Maria; Casanueva, Felipe F.; Seoane, Luisa M. (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2010)
Obesity is currently one of the greatest health problems in industrialized countries, and yet there is no reliable method to fight this pandemic. Bariatric surgery is the most effective method to reduce body weight in morbidly obese patients, suggesting that gastrointestinal tract derived signals are crucial for energy balance regulation. This would indicate that homeostatic mechanisms responsible for body weight maintenance, involving the brain-gut axis are critical for obesity prevention and development. Several descriptive studies have proven the presence of gastric endogenous systems that modulate energetic balance (ghrelin - obestatin system and endocannabinoid system); however, these systems and their interactions are still not well known. The present review describes recent investigations that support the role of the stomach as an energy balance regulator which exerts its effects over known and probably unknown gastrointestinal systems. Additionally, information covering new gastrointestinal derived peptides patents for obesity treatment is provided as well.
Keywords: CCK